Effect of TiC on the high-temperature oxidation behavior of WMoTaNbV refractory high entropy alloy fabricated by selective laser melting. (January 2023) - Chen, Lan; Yang, Zhiwei; Lu, Linkai; Zhang, Xinzhou; Ren, Xudong
Abstract: The refractory high-entropy alloys possess both high melting points and excellent high-temperature properties. As a result, they are expected to become a new generation of high-temperature materials. Along these lines, in this work, selective laser melting (SLM) was used to prepare WMoTaNbV and TiC/WMoTaNbV-based alloys, while the influence of the SLM process parameters on the surface morphology, internal defects distribution and microstructure of the alloy was thoroughly analyzed. On top of that, the long-term high-temperature oxidation behavior of the two alloys at 600°C was studied. The extracted results showed that the process parameters had a serious impact on the surface quality and internal defects of the refractory high-entropy alloys. By optimizing the process parameters, the final surface roughness value of the WMoTaNbV-based alloy was 9.148 μm ( Sa ). On the contrary, the surface roughness value of the TiC/WMoTaNbV compound was 14.218 μm ( Sa ). It is also interesting to notice that the incorporation of TiC could significantly reduce the number of cracks within the TiC/WMoTaNbV alloy. Moreover, the WMoTaNbV-based alloy was mainly composed of dendritic structures, while the TiC/WMoTaNbV-based alloy consisted of cellular structures. The main oxidation products of the WMoTaNbV-based alloy were the Ta16 W18 O94 and Nb14 W3 O47 ternary oxidation products. After the TiC particles were added, the Ti-containing oxidation products such as TiO2, Ti2 Nb10 O29 . etc. within the TiC/WMoTaNbV-based alloy increased significantly, preventing thus effectively the alloy from being seriously oxidized. The cellular structures, carbides and TiO2 phase are helpful in improving the oxidation resistance of the TiC/WMoTaNbV-based alloy. Highlights: The TiC could significantly reduce the number of cracks within the TiC/WMoTaNbV alloy. The oxidation resistance of the TiC/WMoTaNbV was improved. The cellular structures, carbides and TiO2 phase were helpful in improving the oxidation resistance of the TiC/WMoTaNbV alloy.